Community structure of a ten-year old naturally regenerating mangrove stand in Baguingin, Tigbauan, Iloilo. - Animas, Ruphil May Jamotillo (2000.)
The structure of the mangrove community in Tigbauan, was studied using the transect line plot method with seven plots established. Community is described in terms of the following parameters: basal area, stems per hectare, relative density, relative frequency, relative dominance, and importance value of the species and the Shannon Index Diversity. Variations in these parameters are correlated with certain physico-chemical factors--air and water temperature, soil pH, water salinity, land elevation-and the degree of human influence., Three true mangrove species were found in the area: Excoecaria agallocha, Avicennia marina, and Avicennia alba A. marina was found to have the highest relative density of 70.8 relative dominance of 52.35 and importance value of 169.82. A. marina and A. alba have equal relative frequency of 46.67 . Seedlings and samplings of A. marina dominate the area indicating that the community is a young and regenerating stand. Basal area significantly increased from sea to land (53.68 cm. square to 431.66 cm square) and from creek to land ( 8.83 cm square to 366.54 cm square). Shannon Index of Diversity gave a result of 0. The very low diversity index means that there is uneven distribution of individual trees among the species and only a few kinds of species were present and are centered around only two genera, Avicennia species and Excoecaria agallocha.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Mangrove -- Baguingin, Tigbauan, Iloilo. -- Research